The AMOC and its sensitivity to different climate forcings in the range of glacial to modern conditions - Klockmann, Marlene (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
State-of-the-art coupled climate models produce very different states of the Atlantic Meridional Overturning Circulation (AMOC) in simulations of the Last Glacial Maximum (LGM). In particular, many of them fail to capture the shoaling of the North Atlantic Deep Water (NADW) cell, which is indicated by paleo records. The cause for these differences is not yet well understood. Simulations with the Max Planck Earth System Model (MPI-ESM) are used to improve this understanding by studying the sensitivity of the AMOC and the deep Atlantic water masses to different sets of forcings. Analysing the individual contributions of the glacial forcings reveals that the glacial ice sheets cause an increase in the overturning strength and a deepening of the NADW cell, while the low greenhouse gas (GHG) concentrations cause a decrease in overturning strength and a shoaling of the NADW cell. The effect of the orbital configuration is negligible. The effects of the ice sheets and the GHG reduction balance each other in the deep ocean so that no shoaling of the NADW cell occurs in the full glacial state. The mechanism behind the shoaling of the NADW cell is analysed by simulating the AMOC response to different GHG concentrations with linearly decreasing radiative forcing. In order to capture a possible non-linear response, the different GHG concentrations are applied to a setup with glacial ice sheets and to a setup with preindustrial ice sheets. In the simulations with glacial ice sheets, the AMOC decreases linearly with the radiative forcing once the atmospheric pCO2 is below 284 ppm. To simulate a shoaling relative to the preindustrial AMOC state, GHG concentrations below the glacial level are necessary. Antarctic Bottom Water (AABW) needs to become more saline than NADW to achieve the necessary shoaling. Brine release and shelf convection in the Southern Ocean are key processes for the salinity increase of AABW. In the simulations with preindustrial ice sheets, the AMOC strength responds non-linearly to the decreasing radiative ...